Comparing the Effectiveness of Schema Therapy and Acceptance and Commitment Therapy on Suicidal Behaviors in Depressed Patients with Bereavement - Maral Moraveji; Zahra Bagherzadeh Golmakani; Mahdi Akbarzadeh (روانشناسی بالینی و شخصیت)
Introduction: The experience of grief is one of the most painful challenges an individual may face, often leading to symptoms of depression and potentially resulting in self-harming behavior. This study was conducted to compare the effectiveness of schema therapy and acceptance and commitment therapy on the suicidal behaviors of depressed patients experiencing grief.Method: The present study employed a quasi-experimental design featuring a pre-test and post-test, along with a follow-up involving a control group. The statistical population comprised depressed patients experiencing grief who were referred to the Toos Rehabilitation and Treatment Center in Mashhad in 2023. After screening and conducting an initial diagnosis, 45 individuals were selected through purposive sampling and randomly assigned to three groups of 15 participants each: two experimental groups and one control group. Data were collected using depression questionnaires (BDI-II) and assessments of suicidal behaviors (R-SBQ). Initially, all three groups were pre-tested. One experimental group then underwent schema therapy, while the other experimental group received acceptance and commitment therapy for eight 90-minute sessions, held once a week. The control group did not receive any treatment. After the sessions, all three groups underwent post-testing, and follow-up assessments were conducted on all three groups three months later. The data were analyzed using repeated measures analysis of variance (ANOVA) and the Bonferroni post-hoc test.Results: The results indicated that suicidal behaviors decreased from pre-test to post-test and follow-up in both the schema therapy and acceptance and commitment therapy groups (P<0.001). This reduction was more pronounced in the acceptance and commitment therapy group (P<0.001).Discussion and Conclusion: Overall, the results suggest that acceptance and commitment therapy is more effective than schema therapy in reducing suicidal behaviors among depressed patients experiencing grief.It is recommended that specialists in this field utilize Acceptance and Commitment Therapy (ACT) and Schema Therapy to mitigate suicidal behaviors in counseling and treatment centers.